2013
DOI: 10.1128/mbio.00551-13
|View full text |Cite
|
Sign up to set email alerts
|

Load-Dependent Assembly of the Bacterial Flagellar Motor

Abstract: It is becoming clear that the bacterial flagellar motor output is important not only for bacterial locomotion but also for mediating the transition from liquid to surface living. The output of the flagellar motor changes with the mechanical load placed on it by the external environment: at a higher load, the motor runs more slowly and produces higher torque. Here we show that the number of torque-generating units bound to the flagellar motor also depends on the external mechanical load, with fewer stators at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
213
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 180 publications
(235 citation statements)
references
References 29 publications
13
213
0
1
Order By: Relevance
“…Lele et al showed here that the stators themselves dynamically respond to load, and this response was consistently observed even when chemotaxis and rotational switching was removed—it is the stators themselves that engage or disengage with changes in load. The similar observation has also been reported by Tipping et al58 This is presumably because at low load only few stators are required to drive rotation and additional stators simply waste ions 64. However, the mechanism for force‐sensing of the stators remains unknown.…”
Section: Structural Adaptivity Of the Bacterial Flagellar Motorsupporting
confidence: 82%
“…Lele et al showed here that the stators themselves dynamically respond to load, and this response was consistently observed even when chemotaxis and rotational switching was removed—it is the stators themselves that engage or disengage with changes in load. The similar observation has also been reported by Tipping et al58 This is presumably because at low load only few stators are required to drive rotation and additional stators simply waste ions 64. However, the mechanism for force‐sensing of the stators remains unknown.…”
Section: Structural Adaptivity Of the Bacterial Flagellar Motorsupporting
confidence: 82%
“…The BFM has been shown to act as a mechanosensor, increasing the number of stator units in response to higher loads [Lele et al, 2013, Tipping et al, 2013. As the viscosity of the medium rises with addition of sucrose, the speed increase we observed could be due to the incorporation of additional stator units.…”
Section: Origins Of Osmokinesismentioning
confidence: 56%
“…In majority of the traces no obvious steps are observed, suggesting that the increase in motor speed could be due to the increase in PMF with full set of stators present. Here we note that stator engagement with the rotor has been reported as torque dependent [Tipping et al, 2013], where in absence of torque (motor rotation) stators disengage from the rotor. We would then expect stator resurrection during the Recovery Phase shown in SI Appendix Fig.…”
Section: Origins Of Osmokinesismentioning
confidence: 99%
See 1 more Smart Citation
“…The enteric flagellar motor has been suggested to incorporate ∼11 stator complexes that interact with the outer lobe of the C-ring in the cytoplasm and with the peptidoglycan and the P-ring (13). The number of stator complexes incorporated into the enteric motor is proportional to the load on the motor (35,36). Because blotting during the sample vitrification process for cryo-tomographic imaging necessitated imaging in low-viscosity growth medium, we anticipated that a low motor load would result in low stator-complex occupancy and that our subtomogram averaging procedure would not resolve stator complexes.…”
Section: Three Flagellar Motors That Produce Different Torques Are Stmentioning
confidence: 99%